Long-term impacts of antibiotic exposure on the human intestinal microbiota - Cecilia Jernberg; Sonja Löfmark; Charlotta Edlund; Janet Jansson (2010)
Although it is known that antibiotics have short-term impacts on the human microbiome, recent evidence demonstrates that the impacts of some antibiotics remain for extended periods of time. In addition, antibiotic-resistant strains can persist in the human host environment in the absence of selective pressure. Both molecular- and cultivation-based approaches have revealed ecological disturbances in the microbiota after antibiotic administration, in particular for specific members of the bacterial community that are susceptible or alternatively resistant to the antibiotic in question. A disturbing consequence of antibiotic treatment has been the long-term persistence of antibiotic resistance genes, for example in the human gut. These data warrant use of prudence in the administration of antibiotics that could aggravate the growing battle with emerging antibiotic-resistant pathogenic strains.